Assessment of the role of emotions in audiovisual associations through an enactive approach - Costanza Cenerini; Luca Vollero; Nicola Di Stefano; Marco Santonico; Giorgio Pennazza; Flavio Keller (PLoS ONE, 2025)
In the expanding literature on audiovisual associations, the question of how music influences the way a person actively creates an image has received little attention. To address this gap, our study investigated the effect of music-induced emotions on several key parameters that define visual images. Following the hypothesis that creating an image while listening to emotionally evocative music would result in artwork emotionally coherent with the music, we designed a two-phase experiment. During the first phase, participants listened to ten original songs that were composed to evoke a broad range of emotions and were asked to create an image by manipulating both colour (i.e. Saturation, Brightness, Hue) and Geometric parameters (i.e., Shape, Dimension, Spatial Dispersion, and Numerosity). Participants were also required to describe the emotional responses evoked by the songs, assigning scores to a predefined set of nine musical emotions (Amazement, Solemnity, Tenderness, Nostalgia, Calmness, Power, Joyful Activation, Tension, and Sadness). In the second phase, participants viewed images with one parameter set at an extreme value while others remained at intermediate levels and were asked to describe the emotions elicited by the images. This approach enabled us to collect data on the associations between music and images, music and emotions, and images and emotions, thereby assessing whether paired audiovisual contents share the same emotional meaning. Findings reveal that sadness in music influences Brightness and Spatial Dispersion of objects in image creation. Sadness also influences Saturation. Surprisingly, amazement shared many similarities with sadness in terms of influenced parameters, namely Brightness and Dispersion, and was correlated with the colour green, typically evoking solemnity and tenderness. These findings shed novel light on the role of emotions in the mediation of audiovisual associations.